"This house believes that: Sentinel node biopsy alone is better than TAD after NACT for cN+ patients". (February 2023) - Galimberti, Viviana; Ribeiro Fontana, Sabrina Kahler; Vicini, Elisa; Morigi, Consuelo; Sargenti, Manuela; Corso, Giovanni; Magnoni, Francesca; Intra, Mattia; Veronesi, Paolo
Abstract: The increased use of neoadjuvant chemotherapy (NACT) has changed the approach to breast surgery. NACT allows de-escalation of surgery by both increasing breast conservation rates (up to 40%), the initial goal of this chemotherapy, and in particular it permits reduces axillary surgery. Furthermore, in relation to the molecular characteristics of the tumor we can have a pathological complete response (pCR) ranging from 20 to 80%. In clinically node positive (cN+) patients who converted to clinically node-negative (cN0) various prospective studies have demonstrated that the false negative rate (FNR) of the sentinel node biopsy (SNB) were higher than the acceptable 10% and strategies to reduce the FNR in cN + patients are being investigated. But all the effort to reduce the FNR does not have clinical prognostic significance. This has already been demonstrated in the literature in different randomized trials with long term follow up. The 10-year follow-up of our study confirmed our preliminary data that the use of standard SNB without the use of clip is acceptable in cN1/2 patients who become cN0 after NAT and will not translate into a worse outcome. In fact, the axillary recurrences were less than 2%. Similar positive data with different follow up were also confirmed by other studies that used SNB alone without TAD. All these studies, with encouraging results on the follow up, confirm that SN surgery alone for selected patients who have an excellent response to NACT is rationale and not oncologically inferior to AD during a short- and long-term follow-up. Highlights: Sentinel node biopsy alone (SNB) without the use of clip is acceptable in cN + patients who become cN0 NACT SNB alone post NACT will not translate into a worse outcome. Different studies with SNB alone demonstrate good outcome.